2020
DOI: 10.4254/wjh.v12.i6.262
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound in chronic liver disease

Abstract: Endoscopic ultrasound (EUS) is a minimally invasive diagnostic and therapeutic modality with a number of established as well as evolving uses in patients with chronic liver disease. Compared to other diagnostic tools such as cross-sectional imaging or conventional endoscopy, EUS has been shown to increase diagnostic sensitivity and therapeutic success for many clinical scenarios and applications with a low rate of adverse events. In this review, we discuss and focus on the current and growing role of EUS in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 86 publications
0
13
0
1
Order By: Relevance
“…18,19 In addition, endoscopic ultrasonography can also predict the recurrence of esophageal varices after EVL by observing the degree of veins around the esophagus and the collateral veins of the esophagus. 20 In this study, it was found that the more serious the degree of esophageal varices, the wider the diameter of esophageal collateral veins, and there was a significant positive correlation between them. Therefore, when esophageal varices were detected, esophageal collateral veins should be injected at the same time to guide the next step of diagnosis and treatment.…”
Section: Ta B L E 7 Multivariate Ordered Logistic Regression Analysismentioning
confidence: 63%
See 1 more Smart Citation
“…18,19 In addition, endoscopic ultrasonography can also predict the recurrence of esophageal varices after EVL by observing the degree of veins around the esophagus and the collateral veins of the esophagus. 20 In this study, it was found that the more serious the degree of esophageal varices, the wider the diameter of esophageal collateral veins, and there was a significant positive correlation between them. Therefore, when esophageal varices were detected, esophageal collateral veins should be injected at the same time to guide the next step of diagnosis and treatment.…”
Section: Ta B L E 7 Multivariate Ordered Logistic Regression Analysismentioning
confidence: 63%
“…Gao et al 24 bleeding. 27,28 In addition, studies have shown that the diameter of para-esophageal veins is related to a higher recurrence rate of varices. 29,30 However, at present, there are few studies on the prediction of esophageal collateral veins.…”
Section: Ta B L E 7 Multivariate Ordered Logistic Regression Analysismentioning
confidence: 99%
“…Generally, the reduced elastic rebound is highly suggestive for stiffer tissue. This finding, in the context of CLD, indicates liver fibrosis and/or cirrhosis or some other pathological process, such as malignant focal lesions [5][6][7][8]. Elastography modalities currently in use are transient elastography (FibroScan), 2-dimensional shearwave elastography (SWE), acoustic radiation force impulse (ARFI) imaging, real-time elastography (RTE), and magnetic resonance (MR) imaging elastography.…”
Section: Eus Elastographymentioning
confidence: 99%
“…Elastography modalities currently in use are transient elastography (FibroScan), 2-dimensional shearwave elastography (SWE), acoustic radiation force impulse (ARFI) imaging, real-time elastography (RTE), and magnetic resonance (MR) imaging elastography. RTE is different from other ultrasound elastography techniques because it can measure heartbeat-induced strain, which allows relatively objective qualitative and semiquantitative results [5][6][7][8][9][10].…”
Section: Eus Elastographymentioning
confidence: 99%
See 1 more Smart Citation